Tren Pengumpulan Pengetahuan dan Faktor Keberhasilannya: Tinjauan Pustaka Sistematik - Ramadhan, Yudistira; Pratiwi, Maharani Eka; Sensuse, Dana Indra; Lusa, Sofian; Safitri, Nadya; Elisabeth, Damayanti (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Knowledge management (KM) is a systematic approach that facilitates the development, dissemination, and creation of value from information and knowledge within an organization. Knowledge management is deemed the most valuable asset for many organizations. However, the implementation of a knowledge capturing model is still a challenging task. In this research, a Systematic Literature Review (SLR) methodology is employed to identify and analyze diverse approaches to capturing and utilizing knowledge in various organizational domains. The search process is executed across five databases, namely, Scopus, Science Direct, Emerald Insight, Taylor & Francis Online, and IEEE. The study findings reveal a total of 24 knowledge capture methods employed across diverse organizational contexts and knowledge types. Among these methods, the questionnaire was mentioned in 4 articles, an interview in 2 articles, and an expert interview in two articles. The success factors were classified into 20 types, including common knowledge, organizational capabilities, quality of knowledge, trust and acceptance, leadership capabilities, feedback and learning, performance measurement, reward and recognition, efficiency, knowledge management integration, organizational culture, knowledge managers tools and techniques, effectiveness, motivation, information technology, and knowledge management process, training, knowledge representation, and collaboration. Additionally, the identified trending methods and eight key success factors that influence implementation of various knowledge capture models add a new understanding of the critical elements for success in knowledge capture initiatives. This review, in accordance with PRISMA guidelines, provides a foundation for future research efforts in knowledge acquisition and systematic literature review.